Review on polypharmacy and oral health among the elderly - Veiga, Nelio Jorge (2021)
The increase in the elderly population is a factor that occurs worldwide. This fact can be explained by the improvement of living conditions of the populations, advances in medicine, improved sanitation and increase in the community and individual health care. The use of several drugs, self-medication, drug side effects, several drug interactions and decreased quality of life of the population has become an important public health issue. The gradual aging of the population and the increasing prevalence of chronic diseases has led to polypharmacy and the use of drugs that potentially are considered inappropriate for using among the elderly population. Oral diseases, such as periodontal disease, dental caries, lesions in the oral mucosa and xerostomia could be complications associated with polypharmacy among the elderly. It is crucial that the health professional, using his contemporary knowledge, is able to protect the elderly population from complications caused by polypharmacy. The purpose of this article was to highlight the importance of knowledge and recognition of the risks that polypharmacy may represent during dental treatment based on the international scientific literature.